EL BORRACHO BURLADOko euskararen azterketa (1764) - Mendiguren, Xabier (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1987)
In this essay, an analysis is carried out of the Basque used in El Borracho Burlado, a comic opera in Spanish and Basque composed by F. X. Munibe, Count of Peñaflorida, who was one of the founders of the Real Sociedad Bascongada de Amigos del País. The analysis is concerned with graphic, phonic, morphological, syntactic and lexical aspects of the text. There are also some reflections of a sociolinguistic nature. As a basic conclusion, it is pointed out how Peñaflorida felt a need to leave behind the habitual speech of Azkoitia, in order to go in search of a normalised and literary language model such as lacked proper definition at the time. Here the influence of M. de Larramendi's recommendations is quite evident.